Investigating technology integration in English language instruction from 2018 to 2024: A systematic literature review - Wiranata, Sendy; Nasrullah, Nasrullah; Asrimawati, Inayati Fitriyah (Journal of English Language Teaching and Learning (JETLE), 2024)
In-depth research on the use of technology in English language training from 2018 to 2024 is done in this complete systematic review of the literature. It explores how a wide range of digital tools are changing pedagogical methods and highlights the significance of continued professional growth and assistance. The study features the necessity for strategic implementation in line with pedagogical aims to maximize the influence of technology integration on language learning outcomes by integrating previous research and revealing insights into various approaches to technology integration. The results emphasize a general tendency in favor of digital integration, particularly for preservice teachers. In addition, this research also highlights issues revealing educators' differing degrees of familiarity with technology and the scarcity of resources. In this regard, there is an urgency in the inclusivity of digital language literacy exposure and training whether it can elevate English language teachers’ technology integration.